Antifungal Activity of Bee Venom and Sweet Bee Venom against Clinically Isolated Candida albicans - Seung-Bae Lee (Korean Pharmacopuncture Institute, 2016)
Objectives: The purpose of this study was to investigate the antifungal effect of bee venom (BV) and sweet bee venom (SBV) against Candida albicans (C. albicans) clinical isolates. Methods: In this study, BV and SBV were examined for antifungal activities against the Korean Collection for Type Cultures (KCTC) strain and 10 clinical isolates of C. albicans. The disk diffusion method was used to measure the antifungal activity and minimum inhibitory concentration (MIC) assays were performed by using a broth microdilution method. Also, a killing curve assay was conducted to investigate the kinetics of the anti- fungal action. Results: BV and SBV showed antifungal activity against 10 clinical isolates of C. albicans that were cultured from blood and the vagina by using disk diffusion method. The MIC values obtained for clinical isolates by using the broth microdilution method varied from 62.5 μg/ mL to 125 μg/mL for BV and from 15.63 μg/mL to 62.5 μg/mL for SBV. In the killing-curve assay, SBV behaved as amphotericin B, which was used as positive control, did. The antifungal efficacy of SBV was much higher than that of BV. Conclusion: BV and SBV showed antifungal activity against C. albicans clinical strains that were isolated from blood and the vagina. Especially, SBV might be a candidate for a new antifungal agent against C. albicans clinical isolates.